Ability of reconstituted high density lipoproteins to inhibit cytokine-induced expression of vascular cell adhesion molecule-1 in human umbilical vein endothelial cells - Paul W. Baker; Kerry-Anne Rye; Jennifer R. Gamble; Mathew A. Vadas; Philip J. Barter (Journal of Lipid Research, 1999)
Previous studies have shown that both high density lipoproteins (HDL) isolated from human plasma and reconstituted HDL (rHDL) are effective inhibitors of adhesion molecule expression in human endothelial cells. In this study rHDL have been used to investigate whether HDL particle shape, size, apolipoprotein composition or lipid composition are important determinants of the ability of HDL to inhibit the TNF-α induced expression of vascular cell adhesion molecule-1 (VCAM-1) in human umbilical vein endothelial cells (HUVECs). On the basis of these studies it is possible to draw several firm conclusions. i) Neither phospholipid-containing vesicles nor lipid-free apolipoprotein (apo) A-I inhibit VCAM-1 expression in HUVECs. ii) Simple discoidal complexes containing only phospholipid and apoA-I (discoidal (A-I)rHDL) are sufficient to inhibit the TNF-α-induced expression of VCAM-1 in HUVECs. iii) Spherical apoA-I-containing rHDL (spherical (A-I)rHDL) are superior to discoidal (A-I)rHDL as inhibitors. iv) The particle size of spherical (A-I)rHDL has no influence on the inhibition. v) Spherical rHDL that contain apoA-I are superior as inhibitors of VCAM-1 to those containing apoA-II when the rHDL preparations are equated for apolipoprotein molarity. However, when compared at equivalent particle molarities, this difference is no longer apparent. vi) Replacement of cholesteryl esters with triglyceride in the core of spherical (A-I)rHDL has no effect on the ability of these particles to inhibit VCAM-1 expression. From these results it is tempting to speculate that variations in inhibitory activity may contribute to the variations observed in the anti-atherogenicity of different HDL subpopulations.—Baker, P. W., K-A. Rye, J. R. Gamble, M. A. Vadas, and P. J. Barter. Ability of reconstituted high density lipoproteins to inhibit cytokine-induced expression of vascular cell adhesion molecule-1 in human umbilical vein endothelial cells. J. Lipid Res. 1999. 40: 345–353.